Seasonal change in the opportunity for sexual selection - Reichard, M; Smith, C; Bryja, J (Molecular ecology, 2008)
Environmental and population parameters that influence the strength of sexual selection may vary considerably over the course of the reproductive season. However, the potential for sexual selection frequently fails to translate into variation in reproductive success among individuals. We investigated seasonal changes in variation in reproductive success, measured as the opportunity for sexual selection, using parentage analysis in 20 experimental populations of the European bitterling (Rhodeus amarus, Cyprinidae), a small freshwater fish with a promiscuous, resource-based mating system. We showed that although the largest males sired most offspring over the entire reproductive season, variation in reproductive success and hence the opportunity for sexual selection was low at the start of the season but increased significantly at its end. This seasonal difference probably arose from the superior competitive endurance of large males and from a higher temporal clustering of reproductively active females at the start of the breeding season than later in the season. The spatial distribution of oviposition sites had a negligible effect on the variation in reproductive success. We discuss the potential implications of our results for the importance and strength of sexual selection in natural populations.
Keywords: Reproduction; Animals; velikost těla; rozmnožování; Cyprinidae; Female; Seasons; mužské pohlaví; zvířata; sexuální chování zvířat; Body Size; Male; Sexual Behavior, Animal; roční období; ženské pohlaví